2008
DOI: 10.4049/jimmunol.181.7.5001
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Promote Airway Smooth Muscle Cell Differentiation via Autocrine Up-Regulation of TGF-β1

Abstract: Asthma is a major cause of morbidity and mortality worldwide. It is characterized by airway dysfunction and inflammation. A key determinant of the asthma phenotype is infiltration of airway smooth muscle bundles by activated mast cells. We hypothesized that interactions between these cells promotes airway smooth muscle differentiation into a more contractile phenotype. In vitro coculture of human airway smooth muscle cells with β-tryptase, or mast cells with or without IgE/anti-IgE activation, increased airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 39 publications
4
115
0
2
Order By: Relevance
“…TGF-b1 induces the expression of SM22, calponin, a-SMA, MLCK, and Ca 21 pathway proteins in HASM cells, subsequently mediating enhancements in cell stiffness, actin-cytoskeleton reorganization, and contractility (87,104,105). In addition, mast cell-derived TGF-b1 may modulate the phenotype of HASM cells, promoting their differentiation into a more contractile phenotype and subsequently enhancing agonist-induced contraction (106).…”
Section: Contraction Cell Shortening and Cytoskeletal Motorsmentioning
confidence: 99%
“…TGF-b1 induces the expression of SM22, calponin, a-SMA, MLCK, and Ca 21 pathway proteins in HASM cells, subsequently mediating enhancements in cell stiffness, actin-cytoskeleton reorganization, and contractility (87,104,105). In addition, mast cell-derived TGF-b1 may modulate the phenotype of HASM cells, promoting their differentiation into a more contractile phenotype and subsequently enhancing agonist-induced contraction (106).…”
Section: Contraction Cell Shortening and Cytoskeletal Motorsmentioning
confidence: 99%
“…ASMs were stained with rabbit polyclonal anti-NOX4 (Abcam, Cambridge, UK), anti-NOX 1-3 and 5 (Insight Biotechnology, Wembley, UK) indirectly labeled with fluorescein isothiocyanate (FITC; Dako), or a-smooth muscle actin-FITC direct conjugate (Sigma Gillingham, Dorset, UK), or bradykinin B2 receptor indirectly labeled with FITC (BD, Oxford, UK) or isotype controls (Dako) and assessed by flow cytometry (BD FACScan; BD), as previously described (22). ASMs were stained for immunofluorescence with rabbit polyclonal NOX1-5 or anti-superoxide dismutase (SOD)2 (Abcam) or isotype controls, indirectly labeled with FITC, and counterstained with 49,69-diamidino-2 phenylindole (Sigma).…”
Section: Flow Cytometry and Immunofluorescencementioning
confidence: 99%
“…For example, vascular SMCs display reduced levels of contractile filaments following injury to the vessel wall, adopting the so-called synthetic phenotype characterized by an overabundance of rough endoplasmic reticulum (3). On the other hand, recent studies have shown an exaggerated SMC contractile phenotype thought to contribute to disease progression (4,5).…”
mentioning
confidence: 99%